Auditing the Invisible: A Systematic Literature Review on Intangible Asset Verification under ISA 500 - Naghmatun Fadhilah; Nayla Syakirah Riyanti; Jasmin Saidina; Aspahani . (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2026)
The growing complexity of intangible assets in modern financial reporting has created substantial challenges for audit practitioners seeking to obtain sufficient appropriate evidence under International Standard on Auditing (ISA) 500. This Systematic Literature Review (SLR) synthesizes 30 peer-reviewed studies published between 2021 and 2026, applying the PRISMA protocol to investigate how auditors verify intangible assets under ISA 500 and the proposed ED-500 framework. The review identifies four major themes: (1) the evidential challenges posed by fair value and complex estimates inherent to intangible assets; (2) the influence of audit technology and data analytics on audit quality and evidence collection; (3) the impact of intangible asset intensity on audit fees, audit quality, and market perception; and (4) the role of emerging technologies in transforming audit evidence collection. Findings reveal a persistent tension between management discretion in intangible valuation and auditors' capacity to challenge those estimates effectively. The study concludes that the revised ISA 500 must be accompanied by enhanced guidance on specialist reliance, technology-enabled evidence, and skepticism calibration to meaningfully improve intangible asset audit outcomes. Practical implications are drawn for standard-setters, audit firms, and corporate governance mechanisms.